RENCANA PENATAAN KAWASAN DESTINASI WISATA PANTAI LASIANA KOTA KUPANG, PROVINSI NUSA TENGGARA TIMUR - Misella Maria Fransiska Dampung; Suryono Herlambang; Suryadi Santoso (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Lasiana Beach is one of the beaches in Lasiana Sub-district, Kelapa Lima District, Kupang City, East Nusa Tenggara Province. The selection of the Lasiana Beach area is because this area is a tourist area that has become an icon of Kupang City with natural beauty (sea and beach) and agro-tourism (palm trees). As a superior beach, the needs of supporting tourist activities do not match the needs and desires of visitors. This study aims to plan the arrangement of tourist areas that are in accordance with the physical, social and cultural, and economic potential, as well as the needs and desires of visitors. The method used in this research is quantitative and qualitative methods. Has 5 (five) planning concepts, namely first: disaster mitigation (prone to tsunamis and tidal waves), second: environmental preservation (agro-tourism: palm trees and mangroves), third: coastal tourism development (division of coastal and cultural tourism zones), fourth: integration and connectivity within the area (circulation of vehicles and visitors), and fifth: the development of strategic coastal tourism areas on the north coast of Kupang City. With the arrangement will produce a better form of Lasiana Beach. Some of the analyzes conducted are policy / regulatory analysis, environmental carrying capacity analysis, location analysis, site analysis, competitiveness analysis, visitor perception analysis, best practice analysis, analysis of the attractiveness of cultural tourism in the city of Kupang, and analysis of space requirements. Keywords: beach tourism area; beach sports activities and cultural art festival/event; planning AbstrakPantai Lasiana adalah salah satu pantai di Kelurahan Lasiana, kecamatan Kelapa Lima, kota Kupang, Provinsi Nusa Tenggara Timur. Pemilihan kawasan Pantai Lasiana dikarenakan kawasan ini merupakan kawasan wisata yang menjadi icon Kota Kupang dengan keindahan alam (laut dan pantai) dan agrowisata (pohon lontar). Sebagai pantai unggulan, kebutuhan penunjang aktivitas wisata belum sesuai kebutuhan dan keinginan pengunjung. Penelitian ini bertujuan untuk perencanaan penataan kawasan wisata yang sesuai dengan potensi secara fisik, sosial dan budaya, dan ekonomi, serta kebutuhan dan keinginan pengunjung. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dan kualitatif. Memiliki 5(lima) konsep perencanaan yaitu pertama: mitigasi bencana ( rawan bencana tsunami dan gelombang pasang), kedua: pelestarian lingkungan (agrowisata: pohon lontar dan mangrove), ketiga: pengembangan pariwisata pantai (pembagian zona wisata pantai dan budaya), keempat: integrasi dan konektivitas dalam kawasan (sirkulasi kendaraan dan pengunjung), dan kelima: pengembangan kawasan strategis wisata pantai di pesisir Utara Kota Kupang. Dengan adanya penataan akan menghasilkan wujud Pantai Lasiana yang lebih baik. Beberapa analisis yang dilakukan yaitu analisis kebijakan/regulasi, analisis daya dukung lingkungan, analisis lokasi, analisis tapak, analisis competitiveness, analisis persepsi pengunjung, analisis best practice, analisis daya tarik wisata budaya di Kota Kupang, dan analisis kebutuhan ruang.